Avaliação da função renal em pacientes com Anemia Falciforme - Cruz, Sonia Maria Pereira [UNIFESP] (2019)
In the last decades, it has been observed an improvement in survival of sickle cell disease (SCD) patients. Pursuant that, the diagnosis of sickle cell nephropathy has significantly increased and chronic renal disease became an important cause of mortality in older individuals. Early detection and treatment of this nephropathy help us to prevent and delay their related morbidity and mortality. OBJECTIVES: to evaluate the renal function in steady state of SCD. METHODS: Sixty-three patients were included in this study. Their median age was 29 years (range: 19 – 51) and 37 (58.7%) were females. The study group was composed of 56 individuals (88.9%) with SCA and 7 (11.1%) with S-Thal. Complete blood count, reticulocyte count, serum chemistries, serum cystatin C (Cys), quantitative urine albumin and creatinine were ascertained using standard methods. The glomerular filtration rate (GFR) was estimated using the following equations: CKD-EPI, CKD-EPI-Cys, CKD-EPI-Cys+Cr and MDRD. The multiple linear regression model was applied to evaluate the relation of clinical and laboratorial variables with eGFR. RESULTS: Median eGFR was 136.4 mL/min/1.73m2 (range: 90.8 – 181.9). Nine patients (14.3%) had albuminuria. eGFR presented negative correlation with age (r= -0.665, p<0.0001) and significant associations with unconjugated bilirubin, reticulocytes and hemoglobin F. Normal glomerular filtration (NGF) patients (N=14; 22.2%) were compared with GH patients (N=49; 77.8%). GH patients were younger, with lower creatinine and Cys, and higher reticulocytes and unconjugated bilirubin (UB). We observed an important discrepancy in the determination of eGFR among the different equations that was significant (p < 0.0001). The measurement of eGFR was lower in CKD-EPI-Cys and higher in MDRD, with no statistical difference between CKD-EPI and CKD-EPI-Cys+Cr. In the same way, the MDRD equation showed the highest number of individuals with hyperfiltration (90.4%) whereas CKD-EPI-Cys the lowest (6.3%).DISCUSSION: We observed higher GH prevalence (77.8%) than in previous studies, which showed 25-69%. Different eGFR determination methods, study group ages and GFR cutoffs may have been responsible for this difference. Higher prevalence of GH with lower frequency of albuminuria suggests that the sickle cell nephropathy in our patients was at a less advanced stage. Reticulocytes and UB showed associations with eGFR, in agreement with previous studies. eGFR obtained by different equations give a variable prevalence of hyperfiltration in SCD patients. The use of equations with Cys seems to improve the results, but the clinical use of Cys is still restricted. We agree with previous authors that CKD-EPI without adjustment for ethnic is the better equation to daily use in Brazil, although this equation overestimated hyperfiltration. Since GH seems to be a risk factor for development of kidney impairment, our results bring further clarification on this issue.